Preaching the Ecclesiological Gospel Amidst a Syndemic Context - Kim, Seyeom (Religions, 2024)
As the proliferation of new variations of COVID-19 (Coronavirus Disease 2019) continues to increase, it is evident that the COVID-19 pandemic is not over. Indeed, we are living in a world of interrelating and overlapping pandemics—a syndemic. A syndemic accelerates the polarization of access to health care, financial support, and education opportunities in marginalized communities, and the polarization breeds social injustice, violence, and ignorance. What, then, is the Gospel the Church proclaims for those who have experienced the pandemic and are now facing a syndemic? As part of a liturgical response, this paper proposes preaching as a praxis of the ecclesiological Gospel. The ecclesiological Gospel is a term I suggest to highlight the contextual, sacramental, and communal aspects of the Gospel. Highlighting God’s holistic work for salvation represented in baptism and the eucharist, the ecclesiological Gospel yearns to form a church that baptizes people in diversity, that severs evil interconnections, and that welcomes people to the table of hospitality that forms a new covenantal relationship. This paper examines the concept of a syndemic and its significance for preaching in marginalized communities. It contrasts a holistic Gospel perspective with a narrow view, proposes preaching as praxis of the ecclesiological Gospel, and illustrates its application within a particular context in responding to syndemic conditions. I hope this work offers a chance to reorient the meaning of the Gospel and the identity of the Church for people living in fear, grief, and hopelessness, while encouraging them with the unwavering hope revealed in Christ’s suffering, death, and resurrection.